The impact of institutional economics on carrying capacity and sustainable tourism of the subak landscape as a World Cultural Heritage site: A Bayesian network approach - Suasih, Ni Nyoman Reni; Saskara, Ida Ayu Nyoman; Wijaya, Putu Yudy; Yasa, I Made Putra (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2025)
This study aims to analyze the probability of sustainable tourism in Subak Pulagan. Specifically, it examines the probabilistic impact of optimizing tourist visits on tourism carrying capacity and sustainable tourism within the Subak Pulagan landscape. The analysis was conducted using the Bayesian Network (BN) approach to develop a sustainable tourism model that integrates components of institutional economics, destination support factors, carrying capacity, and the World Cultural Heritage (WCH) designation as interrelated variables. Tourism in Subak Pulagan has strong potential for development through village tourism and rural tourism approaches. However, it is crucial to prevent overuse of the carrying capacity, as excessive tourist numbers could undermine the sustainability of tourism in the area. The findings indicate that a significant increase in tourist visits is likely to have a substantial impact on physical and environmental capacities. In contrast, the WCH designation and its associated recognition have not yet made a significant contribution to the sustainable tourism development of Subak Pulagan. As a policy implication, it is recommended to strengthen preventive measures to manage tourism carrying capacity—particularly in the physical and environmental dimensions—to ensure that tourism development supports both heritage preservation and long-term sustainability.